2022
DOI: 10.1111/jam.15532
|View full text |Cite
|
Sign up to set email alerts
|

Water kefir grains vs. milk kefir grains: Physical, microbial and chemical comparison

Abstract: Aims: Although kefir has been known for centuries, there is confusion between the two types of kefir grains, for example, milk kefir (MK) grain and water kefir (WK) grain. This study aimed to unravel the differences and similarities between WK grain and MK grain.Methods and Results: Microbiological analyses, identification of grains microbiota and enumeration of microbiological content of the grains as well as scanning electron microscope (SEM) imaging, dry matter, protein, ash, and mineral content, and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 57 publications
0
15
1
Order By: Relevance
“…Furthermore, researchers reported that water kefir grains consisted of roughly 39% Lactobacillus sp., 31% Lactococcus sp. and 30% yeasts ( Gökırmaklı and Güzel-Seydim, 2022 ). All these studies reflect the fact that water kefir is usually made in an artisanal manner and the fermentation environment is generally variable.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers reported that water kefir grains consisted of roughly 39% Lactobacillus sp., 31% Lactococcus sp. and 30% yeasts ( Gökırmaklı and Güzel-Seydim, 2022 ). All these studies reflect the fact that water kefir is usually made in an artisanal manner and the fermentation environment is generally variable.…”
Section: Introductionmentioning
confidence: 99%
“…There are previous studies that reported the effects of milk kefir against IBS (Seo et al ., 2018; Yılmaz et al ., 2019; Curciarello et al ., 2021). On the other hand, it was clearly explained in other previous studies that microbiota and metabolites of WK and milk kefir significantly differ (Guzel‐Seydim et al ., 2021; Gökırmaklı & Güzel‐Seydim, 2022). The ameliorative effect of WK against IBS was revealed in this pioneer study.…”
Section: Discussionmentioning
confidence: 99%
“…in the diet had the strongest influence (Dai et al ., 2013). Lactobacillus species, particularly Lactobacillus paracasei , L. hilgardii , and L. nagelii , are prevalent in WK (Gökırmaklı & Güzel‐Seydim, 2022). According to Marlicz et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Consumers are increasingly concerned about incorporating healthy foods into their diets, increasing the demand for probiotics, prebiotics, and functional fermented beverages. Water kefir is produced by fermentation of sugar solution with water kefir grains containing lactic acid bacteria such as Lactobacillus paracasei, Lactobacillus casei, Lactobacillus hilgardii, Lactobacillus nagelii, and yeasts like S. cerevisiae (Gökırmaklı & Güzel-Seydim, 2022). With potential health benefits, water kefir is gaining popularity as a fermented food using non-dairy substrates like vegetables, fresh/dried fruits, and plant-based milk.Thus, it also stands out as an important source of probiotics for both vegans and allergic individuals.
…”
mentioning
confidence: 99%